1996
DOI: 10.1021/es950731c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature, Ionic Strength, Background Electrolytes, and Fe(III) on the Reduction of Hexavalent Chromium by Soil Humic Substances

Abstract: The rate of hexavalent chromium reduction by soil humic substances (SHSs) was investigated in aqueous solutions where the temperature, ionic strength, background electrolyte, [Fe(III)], and [Cr(III)] were independently varied. Rate experiments were conducted with an excess of SHS over Cr(VI). An Arrenhius plot for the reduction of Cr(VI) by a soil fulvic acid and a soil humic acid indicates that the activation enthalpies for oxidation of these substances are nearly the same (63 ± 1 and 61 ± 3 kJ mol-1, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
1
14

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(150 citation statements)
references
References 32 publications
8
127
1
14
Order By: Relevance
“…These results are similar to those found in many other studies (Zhilin et al 2004;Deiana et al 2007), indicating that reductions of Cr(VI) by organic materials can be accelerated at low pH. As the pH of Pinchen soils increased to 5.0 and 6.2 from 4.5 by the adding of CaCO 3 , this probably took them out of the most favorable pH range for Cr(VI) reduction (Wittbrodt and Palmer 1996;Schlautman and Han 2001). However, for the Neipu soils, there was no dependence of pH on the extent of Cr(VI) reduction.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…These results are similar to those found in many other studies (Zhilin et al 2004;Deiana et al 2007), indicating that reductions of Cr(VI) by organic materials can be accelerated at low pH. As the pH of Pinchen soils increased to 5.0 and 6.2 from 4.5 by the adding of CaCO 3 , this probably took them out of the most favorable pH range for Cr(VI) reduction (Wittbrodt and Palmer 1996;Schlautman and Han 2001). However, for the Neipu soils, there was no dependence of pH on the extent of Cr(VI) reduction.…”
supporting
confidence: 90%
“…The most favorable solution pH for Cr (VI) reduction by organic materials ranges from 1 to 4 (Wittbrodt and Palmer 1996). Zhilin et al (2004) showed that Cr(VI) was reduced by peat and coal humic substances at pH 5.4, but not at pH 9.2.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of a combined reduction by the co-presence of Fe(II) and HAs are hereby different from the kinetics of experiments where only Fe(II) or only HAs were available [22,23]. It is claimed that this effect is dependent on the specific type of humic substance [22] and it is also limited by the lower solubility of Fe(III) at higher pH values, which would lead to a precipitation of ferric hydroxide(s), so that no further recycling of Fe can take place [24]. Therefore, there is a need for further investigation, regarding the effect of HAs or of natural organic matter on Cr(VI) and on total chromium removal by the application of Fe(II) reductive precipitation.…”
Section: Introductionmentioning
confidence: 87%
“…However, at the tested pH range, Fe(III) is practically insoluble (with the respective Ksp = 6 × 10 −38 [8]) and is therefore removed from the solution, indicating that redox cycling might not take place in this case [24].…”
Section: [Cr(vi)]:[fe(ii)])mentioning
confidence: 99%
“…According to the data, Cr and OM appearance at the same statistical analysis factor (Table V) proves a Cr preferred association to organic fraction of the sequential extraction procedure (step 3). The preferential association of Cr to the oxidizable phase indicated that most of that metal could be retained in the sediments in the trivalent state, less toxic, and bound to organic matter (Armienta et al 1996, Wittbrodt andPalmer 1996). From the Portão stream, we extracted 1,039 mg/kg in the oxidizable step, equivalent to 81% of the total concentration of this metal.…”
Section: Total Contents and Metal Fractionationmentioning
confidence: 99%